Neurodevelopmental outcomes in children exposed prenatally to levetiracetam - Bshra A. Alsfouk (SAGE Publishing, 2022)
Some old antiseizure medications (ASMs) pose teratogenic risks, including major congenital malformations and neurodevelopmental delay. Therefore, the use of new ASMs in pregnancy is increasing, particularly lamotrigine and levetiracetam. This is likely due to evidence of low risk of anatomical teratogenicity for both lamotrigine and levetiracetam. Regarding neurodevelopmental effects, lamotrigine is the most frequently investigated new ASM with information available for children up to 14 years of age. However, fewer data are available for the effects of levetiracetam on cognitive and behavioral development, with smaller cohorts and shorter follow-up. The aim of the present review was to explicate neurodevelopmental outcomes in children exposed prenatally to levetiracetam to support clinical decision-making. The available data do not indicate an increased risk of abnormal neurodevelopmental outcomes in children exposed prenatally to levetiracetam. Findings demonstrated comparable outcomes for levetiracetam versus controls and favorable outcomes for levetiracetam versus valproate on global and specific cognitive abilities, and behavioral problems. In addition, the available evidence shows no significant dose-effect association for levetiracetam on neurodevelopmental outcomes. However, this evidence cannot be determined definitively due to the limited numbers of exposures with relatively short follow-up. Therefore, further research is required. Plain Language Summary Antiseizure medications (ASMs) are medicines that inhibit the occurrence of seizures. Levetiracetam is a new ASM. Some old ASMs are linked with an increased risk of physical birth abnormalities and adverse effects on the child's brain development. Therefore, the use of new ASMs in pregnancy is increasing, especially lamotrigine and levetiracetam. This is likely due to evidence of low risk of birth abnormalities for both lamotrigine and levetiracetam. Regarding effects on development of the brain, lamotrigine is the most frequently examined new ASM with information available for children up to 14 years of age. However, fewer data are available for the effects of levetiracetam on cognitive and behavioral development. Also, levetiracetam studies were smaller and shorter compared with studies investigating lamotrigine effects. The aim of this article was to review the child's brain development effects after exposure to levetiracetam during pregnancy. The available data do not suggest an increased risk of the child having learning or thinking difficulties. Findings demonstrated comparable outcomes for levetiracetam versus controls (i.e. children unexposed to levetiracetam), and favorable outcomes for levetiracetam versus valproate. In addition, the available evidence shows no link between the higher dose of levetiracetam and an increased risk of adverse effects on the child's brain development. However, this evidence cannot be determined definitively due to the limited numbers of children exposed to levetiracetam with relatively short duration of follow-up. Therefore, further research is required.